CHALLENGES FOR MICRO-ENTERPRISE AND INCOME TAXPAYERS IN 2023 - SORIN-CONSTANTIN DEACONU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2023)
Entities are registered in Romania in the fiscal vector in 2023 as income taxpayers or profit taxpayers. Due to the legislative changes, the execution of the financial year 2023 radically changes the status of the entities, and each economic agent must be separately analyzed to be included in the correct fiscal vector. The classification is made according to several criteria. One of the criteria is that of an employee or its equivalent. The quality of employees implies the conclusion of an administration contract, which is highlighted in REVISAL. The management contract only requires an act that refers to the entity's management. However, a minimum wage per economy is required, which in Romania at present is 3,000 lei.